Pembelajaran Matematika Dengan Menggunakan Media Berhitung di SD Negeri 327 Sinunukan dalam Meningkatkan Pemahaman Siswa - Siregar, Torang; Adinda, Anita (Jurnal Didaktika Pendidikan Dasar, 2025)
Mathematics learning, particularly in elementary schools, requires effective strategies to enhance students’ comprehension. One such strategy is the use of counting media. Counting is closely related to numbers and is a fundamental component of mathematics, as it involves managing and processing numerical information. Since mathematics is abstract, consistent, logical, and deductive in nature, the use of appropriate media can help bridge students’ understanding of these abstract concepts. Counting skills are also widely applied in other disciplines such as physics, biology, chemistry, and economics, making them essential for students’ broader academic development. In mathematics education, students are trained to develop understanding through experience, abstraction, and logical reasoning. However, this process must be adjusted to the developmental stage and abilities of the learners. The integration of counting media in mathematics learning can provide concrete experiences that foster conceptual understanding, reduce learning difficulties, and stimulate active participation. Therefore, utilizing counting media in elementary school mathematics not only strengthens students’ basic numeracy skills but also supports their reasoning abilities and logical thinking. Ultimately, it contributes to the smooth and effective implementation of mathematics learning in schools, laying a strong foundation for future learning.